2017
DOI: 10.1039/c7sm01412k
|View full text |Cite
|
Sign up to set email alerts
|

Interpenetrating polymer networks of liquid-crystalline azobenzene polymers and poly(dimethylsiloxane) as photomobile materials

Abstract: We developed photomobile polymer materials with interpenetrating polymer network (IPN) structures composed of crosslinked liquid-crystalline azobenzene polymer (PAzo) and poly(dimethylsiloxane) (PDMS). By introducing PDMS into a PAzo template network, IPN was formed without disturbing the alignment of mesogens in the PAzo network. The films showed macroscopic bending behavior upon irradiation with UV and visible light. Although the IPN film showed a phase separated structure, the bending speed was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…In a practical point of view, a large variation of Young's modulus is helpful to design adequate materials depending on the purpose of use. It has been also found that Young's modulus can be controlled by introducing amorphous polymer components into CLCPs to form interpenetrating polymer networks . Photoactuation based on the change in T g along with photoisomerization has been demonstrated as well …”
Section: Structures Of Photomobile Polymer Materials From Nano To Macromentioning
confidence: 93%
“…In a practical point of view, a large variation of Young's modulus is helpful to design adequate materials depending on the purpose of use. It has been also found that Young's modulus can be controlled by introducing amorphous polymer components into CLCPs to form interpenetrating polymer networks . Photoactuation based on the change in T g along with photoisomerization has been demonstrated as well …”
Section: Structures Of Photomobile Polymer Materials From Nano To Macromentioning
confidence: 93%
“…New material systems (such as IPNs) can be developed to obtain materials with favorable actuation stress and fast reversible deformation. [132,133] Another solution is to adopt a hybrid structure composed of both stiff and soft components. [134] Second, for most cases where the actuation is essentially thermally stimulated, the mechanical response of an LCN-based soft robot is related to its phase-transition behavior and the temperature-switching approach.…”
Section: Perspectivementioning
confidence: 99%
“…New material systems (such as IPNs) can be developed to obtain materials with favorable actuation stress and fast reversible deformation. [ 132,133 ] Another solution is to adopt a hybrid structure composed of both stiff and soft components. [ 134 ]…”
Section: Perspectivementioning
confidence: 99%
“…For the most‐known example, Gong's group has developed the double network gel (DN gels) composed of two kinds of network with different strength, where these two kinds of cross‐linked networks are interpenetrating with each other. Thus DN gels are a special class, but can be categorized and called as the interpenetrating polymer network (IPN). In their first report, the first network is kept flexible and highly stretchable while the second network is designed to be brittle against deformation.…”
Section: Summary Of Mechanical Propertiesmentioning
confidence: 99%